2023
DOI: 10.1039/d2cp05305e
|View full text |Cite
|
Sign up to set email alerts
|

A unified reaction network on the formation of five-membered ringed polycyclic aromatic hydrocarbons (PAHs) and their role in ring expansion processes through radical–radical reactions

Abstract: Exploiting a chemical microreactor in combination with an isomer-selectively product identification through fragment-free photoionization utilizing tunable vacuum ultraviolet (VUV) light in tandem with the detection of the ionized molecules by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…356 Li et al showed that the interaction of acetylene with methylene-substituted aromatic compounds carrying a hydrogen atom at the ortho-position of the ring can provide a universal pathway for accessing fivemembered aromatic compounds (C 13 H 10 , as indicated above) at elevated temperatures. 357 These reactions were carried out in a high-temperature chemical microreactor at 1300 K. In addition to the experiments, corresponding calculations of the energies and molecular parameters of various intermediates and transition states were performed. These calculations have shown that tricyclic PAHs can be formed via a barrierless HAVA mechanism in cold molecular clouds at temperatures of approximately 10 K. 358 An interesting experimental study of the formation of PAHs with five-membered rings under high-temperature conditions was carried out by Necula and Scott.…”
Section: Mechanism Of Formation Of Pahs Withmentioning
confidence: 99%
See 1 more Smart Citation
“…356 Li et al showed that the interaction of acetylene with methylene-substituted aromatic compounds carrying a hydrogen atom at the ortho-position of the ring can provide a universal pathway for accessing fivemembered aromatic compounds (C 13 H 10 , as indicated above) at elevated temperatures. 357 These reactions were carried out in a high-temperature chemical microreactor at 1300 K. In addition to the experiments, corresponding calculations of the energies and molecular parameters of various intermediates and transition states were performed. These calculations have shown that tricyclic PAHs can be formed via a barrierless HAVA mechanism in cold molecular clouds at temperatures of approximately 10 K. 358 An interesting experimental study of the formation of PAHs with five-membered rings under high-temperature conditions was carried out by Necula and Scott.…”
Section: Mechanism Of Formation Of Pahs Withmentioning
confidence: 99%
“…In addition, it has recently been shown that the reaction of a benzyl radical with a phenyl (C 6 H 5 ) radical is a pathway for the formation of another important PAH containing a five-membered ring, 9 H -fluorene . Li et al showed that the interaction of acetylene with methylene-substituted aromatic compounds carrying a hydrogen atom at the ortho -position of the ring can provide a universal pathway for accessing five-membered aromatic compounds (C 13 H 10 , as indicated above) at elevated temperatures . These reactions were carried out in a high-temperature chemical microreactor at 1300 K. In addition to the experiments, corresponding calculations of the energies and molecular parameters of various intermediates and transition states were performed.…”
Section: Mechanisms For the Formation Of Polyaromatic Compounds In Spacementioning
confidence: 99%
“…Here, we explore experimentally and computationally to what degree the gas-phase reaction of the resonantly stabilized fulvenallenyl radical (C 7 H 5 · ) with allene (H 2 CCCH 2 ) and methylacetylene (CH 3 CCH) competes with the fulvenallenyl (C 7 H 5 · )propargyl (C 3 H 3 · ) system in the preparation of the 10π-Hückel aromatic C 10 H 8 isomers–fundamental molecular building blocks in molecular mass growth processes of carbonaceous nanostructures. , Formed through ring annulation within a high-temperature chemical microreactor, the reaction products were entrained in a supersonic molecular beam and analyzed isomer-specifically via fragment-free photoionization of the neutral products exploiting tunable VUV light in conjunction with a reflection time-of-flight mass spectrometer (Re-TOF-MS) . We performed electronic structure calculations on the pertinent potential energy surface (PES), followed by the evaluation of the reaction rate constants and kinetic modeling of the physicochemical processes in the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we provide persuasive testimony on the first gas phase preparation of the azulene molecule (C 10 H 8 ) along with its naphthalene isomer (C 10 H 8 ) initiated through the reaction of two resonantly stabilized free radicals – fulvenallenyl and propargyl – via de-factor ring annulation within a chemical microreactor 40–42 via the novel Fulvenallenyl Addition Cyclization Aromatization (FACA) reaction mechanism. The reaction products were sampled in a molecular beam via electron ionization 43–45 and isomer-specifically via fragment-free photoionization of the neutral products exploiting tunable vacuum ultraviolet (VUV) light followed by detection of the ionized molecules in a reflection time-of-flight mass spectrometer 41,46 (Re-TOF-MS; Fig. S1 and S2, ESI†).…”
Section: Introductionmentioning
confidence: 99%
“…and propargyl ðC 3 H 3 Þvia de-factor ring annulation within a chemical microreactor [40][41][42] via the novel Fulvenallenyl Addition Cyclization Aromatization (FACA) reaction mechanism. The reaction products were sampled in a molecular beam via electron ionization [43][44][45] and isomer-specically via fragment-free photoionization of the neutral products exploiting tunable vacuum ultraviolet (VUV) light followed by detection of the ionized molecules in a reection time-of-ight mass spectrometer 41,46 (Re-TOF-MS; Fig. S1 and S2, ESI †).…”
Section: Introductionmentioning
confidence: 99%